Magnesium-doped sodium ferric fluorophosphate material double-coated with sodium phosphate and carbon layer as well as preparation method and application of magnesium-doped sodium ferric fluorophosphate material

Through the technology of magnesium doping and double-coating of sodium phosphate and carbon layer, the problem of poor rate performance and insufficient cycle performance of sodium ferrous phosphate in sodium ion batteries is solved, and the energy density and cycle stability of the material are improved.

CN119725466AActive Publication Date: 2025-03-28HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411926202.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Sodium ferric fluorine phosphate has poor rate performance and insufficient cycle performance in sodium ion batteries.

Method used

Through magnesium doping and double-coating of sodium phosphate and carbon layer, the electronic structure is adjusted, the sodium ion migration efficiency is improved, and the structural stability and conductivity of the material are enhanced.

Benefits of technology

It significantly improves the energy density and cycle stability of the material, improves the rate performance and the interface stability of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725466A_ABST
    Figure CN119725466A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium phosphate and carbon layer double-coated magnesium-doped sodium ferric phosphate fluorophosphate material and a preparation method and application thereof, the magnesium-doped sodium ferric phosphate fluorophosphate material takes Na2FexMgyPO4F as an inner core, the surface of the inner core is coated with a sodium phosphate layer, the outermost layer is a conductive carbon layer, Fe is + 2, y is greater than or equal to 0.05 and less than or equal to 0.10, and x + y is equal to 1. According to the preparation method, surface phosphate enrichment is realized through one-time ball milling in a manner of excessively adding a phosphorus source and a sodium source, molten sodium phosphate is generated through presintering and coats the surfaces of presintered particles, and the cycle performance of the material is improved; carbon layer coating is achieved through high-temperature sintering, and the electronic conductivity is improved. A uniform sodium phosphate and carbon double coating layer is formed on the surface of the material in a one-time ball milling and sintering mode, so that the interface side reaction between the material and an electrolyte can be reduced, and the problems of low discharge capacity, poor rate capability and the like caused by lower intrinsic conductivity of the material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials for sodium ion batteries, and relates to a sodium iron fluorophosphate material and a preparation method thereof, and specifically relates to a magnesium-doped sodium iron fluorophosphate material double-coated with sodium phosphate and a carbon layer, a preparation method thereof, and an application thereof in sodium ion batteries. Background Art

[0002] As traditional fossil energy sources are becoming increasingly depleted, various new types of renewable energy have broad application prospects. Lithium-ion batteries have been widely used in production and life due to their high specific energy and long cycle characteristics, but lithium resources have problems such as uneven distribution and difficulty in mining. As an emerging secondary battery, sodium-ion batteries have the advantages of abundant resources, low prices, and good safety. Their key technologies are not much different from those of lithium-ion batteries, and they have a good technical foundation. In addition, sodium-ion batteries can also achieve discharge in a wide temperature range and fast charging and discharging. Therefore, sodium-ion batteries are becoming the main choice for large-scale energy storage power stations with relatively low energy density requirements.

[0003] At present, common sodium-ion battery cathode materials still face many challenges such as low energy density and poor cycle performance. Among them, layered iron-based fluorophosphate Na2FePO4F is a potential candidate cathode material with a two-dimensional sodium ion transmission channel, a narrow and smooth charge and discharge curve, low battery management difficulty, and is suitable for large-scale grid energy storage. However, it still has problems such as low intrinsic conductivity, poor rate, low energy density, and poor cycle stability, which limit the large-scale production and commercial application of this material. Weakly electronegative magnesium doping is conducive to inducing charge redistribution, adjusting the electronic structure, and increasing conductivity. Carbon coating can improve the electronic conductivity of the material and improve the rate performance of the material, but simple carbon coating is not protective enough for the material and cannot avoid side reactions between the matrix material and the electrolyte. Multi-layer coating can achieve multiple effects and bring significant performance improvements. Usually, the coating materials of the cathode are mainly oxides, fluorides, phosphates, metal elements, etc. Sodium phosphate, as a good coating layer for the cathode material, can greatly improve the material performance. Summary of the invention

[0004] In order to solve the problems of poor rate performance and insufficient cycle performance of the current sodium ferric fluorophosphate materials, the present invention provides a magnesium-doped sodium ferric fluorophosphate material double-coated with sodium phosphate and a carbon layer, and a preparation method and application thereof. The present invention prepares a magnesium-doped sodium ferric fluorophosphate core Na2Fe x Mg yPO4F, in which Fe is +2, 0.05≤y≤0.10, x+y=1, adjusts the electronic structure, reduces the energy barrier for sodium ion migration, and improves the intrinsic conductivity of the material; the sodium phosphate coating layer spontaneously formed on the surface helps to isolate the electrolyte, improve the ion conductivity and cycle performance; the outermost carbon layer is beneficial to improving the electronic conductivity of the material and improving the rate performance of the material; the three are combined and achieved through a one-step ball milling and sintering process, with a simple process and broad application prospects.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer, with Na2Fe x Mg y PO4F is the inner core, the inner core surface is covered with a sodium phosphate layer, and the outermost layer is a conductive carbon layer, wherein Fe is +2, 0.05≤y≤0.10, and x+y=1.

[0007] A method for preparing the above-mentioned sodium phosphate and carbon layer double-coated magnesium-doped sodium fluorophosphate material, which realizes the preparation of the double-coated magnesium-doped sodium fluorophosphate material by a one-step method, specifically comprising the following steps:

[0008] Step 1: Mixing:

[0009] A sodium source, an iron source, a magnesium source, a phosphorus source, a fluorine source and a carbon source are mixed in proportion to obtain a solid raw material mixture, wherein:

[0010] The ratio of each element in the solid raw material mixture is Na:Fe:Mg:P:F=2-2.5:0.85-0.99:0.01-0.15:1-1.5:1-1.5, and the carbon source accounts for 10-20% of the total mass of the sodium source, the iron source, the magnesium source, the phosphorus source and the fluorine source;

[0011] The sodium source is at least one of sodium fluoride, sodium acetate, sodium carbonate, sodium bicarbonate, sodium citrate, sodium oxalate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium isopropoxide, sodium carboxymethyl cellulose, sodium oleate, sodium ascorbate, and sodium alginate;

[0012] The iron source is at least one of ferrous oxalate, ferrous sulfate, ferrous chloride, ferric phosphate, ferric oleate, ferric citrate, ferric tartrate, and sodium ferric ethylenediaminetetraacetate;

[0013] The magnesium source is at least one of magnesium oxide, magnesium carbonate, magnesium chloride, magnesium phosphate, magnesium oxalate, magnesium gluconate, magnesium acetate, magnesium citrate, and magnesium methoxide;

[0014] The phosphorus source is at least one of phosphoric acid, sodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate;

[0015] The fluorine source is at least one of sodium fluoride and hydrofluoric acid;

[0016] The carbon source is at least one of glucose, sucrose, ascorbic acid, graphite, carbon nanotubes, polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, sodium carboxymethyl cellulose, phytic acid, stearic acid, and urea;

[0017] Step 2: Mechanical ball milling:

[0018] The solid raw material mixture and ball milling beads in step 1 are added to a ball mill for ball milling, and the ball milling product is vacuum dried, wherein:

[0019] The mass ratio of the ball milling beads to the solid raw material mixture is 8 to 10:1;

[0020] The ball milling may be performed without adding a liquid medium, or may be performed with a liquid medium, wherein the medium includes one or more of water, ethanol, oleic acid, and N-methylpyrrolidone;

[0021] The ball milling speed is 300-500 rpm, the time is 6-8 hours, and the material temperature is controlled below 40°C;

[0022] The vacuum drying temperature is 60-100°C and the time is 8-14 hours. The drying time is adjusted according to the amount of material. The target material is required to be dry and white or light yellow as a whole.

[0023] Step 3: Sintering:

[0024] Under the protection of inert gas, low-temperature pre-sintering is first performed, and then the temperature is raised in the same furnace for secondary sintering, and finally a magnesium-doped sodium fluoroferric phosphate material double-coated with a carbon layer and a sodium phosphate layer is obtained, wherein:

[0025] The low-temperature pre-sintering process is as follows: first, pre-flow protective gas at room temperature for 0.5 to 2 hours, then heat to 350 to 450°C, calcine at this temperature for 2 to 6 hours, and control the heating rate to be 3 to 5°C / min;

[0026] The calcination temperature of the secondary sintering is 550-650°C, the calcination time is 8-12h, and the heating rate is controlled to be 3-5°C / min;

[0027] The entire sintering process of the low-temperature pre-sintering and the secondary sintering is carried out under a protective atmosphere;

[0028] The inert gas is one or more of argon, hydrogen, nitrogen and helium.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. The present invention improves the electronic conductivity of the phosphate material by doping with magnesium and coating with sodium phosphate on the basis of the sodium iron fluorophosphate Na2FePO4F material, and at the same time enhances the structural stability of the material, so that the positive electrode active material has both high energy density and cycle stability. Among them, magnesium doping can effectively improve the structural strength of the material, adjust the ion transmission energy barrier, and can be anchored between the lattices to widen the lattice size and improve the sodium ion transmission rate; the sodium phosphate coating layer is beneficial to inhibit surface precipitation, enhance ion conductivity, and improve the cycle stability of the material.

[0031] 2. The present invention achieves surface phosphate enrichment by excessive addition of phosphorus source and sodium source through one ball milling, generates molten sodium phosphate through pre-sintering and coats the surface of pre-sintered particles to improve the material's cycle performance; and achieves carbon layer coating through high-temperature sintering to improve electronic conductivity. The one-time ball milling and sintering method forms a uniform double coating of sodium phosphate and carbon on the surface of the material, which can reduce the interface side reaction between the material and the electrolyte, and improve the problems of low discharge capacity and poor rate performance caused by the low intrinsic conductivity of the material.

[0032] 3. The present invention achieves double-layer coating in one step by adjusting the components and the calcination procedure during the ball milling process. The coating is denser and synergistic with magnesium doping, which improves the stability of the positive electrode structure. The preparation process is simple and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of the structure of magnesium-doped sodium fluoroferric phosphate double-coated with sodium phosphate and a carbon layer prepared in Example 1;

[0034] Figure 2 This is a SEM image of magnesium-doped sodium fluoroferric phosphate double-coated with sodium phosphate and a carbon layer prepared in Example 1;

[0035] Figure 3 A comparison chart of the cycle curves of the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer prepared in Example 1 and the undoped sodium fluoroferric phosphate and uncoated sodium fluoroferric phosphate;

[0036] Figure 4 This is a comparison chart of the charge and discharge curves of the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer prepared in Example 1 and the undoped and uncoated sodium fluoroferric phosphate. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0038] Embodiment 1:

[0039] This embodiment provides a magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and a carbon layer, such as Figure 1 As shown, the material is divided into three layers, the inner layer is Na2Fe 0.95 Mg 0.05 PO4F, a sodium phosphate layer coated in the middle, a conductive carbon layer on the surface, wherein Fe is +2, 0.05≤y≤0.10, x+y=1, and the preparation method comprises the following steps:

[0040] 1) Sodium oleate, ferrous oxalate, magnesium citrate, diammonium hydrogen phosphate and sodium fluoride are mixed in a proportion of Na:Fe:Mg:P:F=2.3:0.95:0.05:1.1:1; 5% by weight of ascorbic acid and 5% by weight of stearic acid are added to the mixture after weighing.

[0041] 2) The mixture was ball-milled in N-methylpyrrolidone at a speed of 450 rpm for 8 h, and then vacuum-dried at 90° C. for 12 h.

[0042] 3) After vacuum drying, sintering is carried out step by step under the protection of hydrogen and argon atmosphere: first, pre-pass protective gas at room temperature for 1 hour, then heat up to 350°C at a heating rate of 5°C / min, calcine at this temperature for 3 hours, then heat up to 650°C at a heating rate of 5°C / min, calcine at this temperature for 12 hours, and finally obtain uniformly carbon-coated sodium phosphate and carbon layer double-coated Mg-doped sodium fluorophosphate material.

[0043] Embodiment 2:

[0044] This embodiment provides a magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and a carbon layer, such as Figure 1 As shown, the material is divided into three layers, the inner layer is Na2Fe 0.98 Mg 0.02 PO4F, a sodium phosphate layer coated in the middle, a conductive carbon layer on the surface, wherein Fe is +2, 0.05≤y≤0.10, x+y=1, and the preparation method comprises the following steps:

[0045] 1) Sodium citrate, ferric phosphate, magnesium acetate, diammonium hydrogen phosphate and sodium fluoride are mixed in a proportion of Na:Fe:Mg:P:F=2.12:0.98:0.02:1.04:1; 5% by weight of ascorbic acid and 10% by weight of phytic acid are added to the mixture after weighing.

[0046] 2) The mixture was ball-milled in N-methylpyrrolidone at a speed of 450 rpm for 8 h, and then vacuum-dried at 90° C. for 12 h.

[0047] 3) After vacuum drying, sintering is carried out step by step under the protection of argon atmosphere: first, pre-pass protective gas at room temperature for 1 hour, then heat up to 400°C at a heating rate of 3°C / min, calcine at this temperature for 3 hours, then heat up to 600°C at a heating rate of 3°C / min, calcine at this temperature for 12 hours, and finally obtain uniformly carbon-coated sodium phosphate and carbon layer double-coated Mg-doped sodium fluoroferric phosphate material.

[0048] Embodiment 3:

[0049] This embodiment provides a magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and a carbon layer, such as Figure 1 As shown, the material is divided into three layers, the inner layer is Na2Fe 0.98 Mg 0.02 PO4F, a sodium phosphate layer coated in the middle, a conductive carbon layer on the surface, wherein Fe is +2, 0.05≤y≤0.10, x+y=1, and the preparation method comprises the following steps:

[0050] 1) Sodium phosphate, ferric tartrate, magnesium gluconate, diammonium hydrogen phosphate and sodium fluoride are mixed in a proportion of Na:Fe:Mg:P:F=2.12:0.98:0.02:1.04:1; 5% by weight of ascorbic acid and 10% by weight of polyvinyl alcohol are added to the mixture after weighing.

[0051] 2) The mixture was ball-milled in N-methylpyrrolidone at a speed of 450 rpm for 8 h, and then vacuum-dried at 90° C. for 12 h.

[0052] 3) After vacuum drying, sintering is carried out step by step under the protection of nitrogen atmosphere: first, pre-pass protective gas at room temperature for 1 hour, then heat up to 450°C at a heating rate of 5°C / min, calcine at this temperature for 3 hours, then heat up to 650°C at a heating rate of 5°C / min, calcine at this temperature for 12 hours, and finally obtain uniformly carbon-coated sodium phosphate and carbon layer double-coated Mg-doped sodium fluoroferric phosphate material.

[0053] Comparative Example 1:

[0054] The difference between this comparative example and Example 1 is that magnesium doping is not performed.

[0055] Comparative Example 2:

[0056] The difference between this comparative example and Example 1 is that the phosphorus and sodium in the raw materials are in a normal stoichiometric ratio, that is, no sodium phosphate coating is performed.

[0057] Comparative Example 3:

[0058] The difference between this comparative example and Example 1 is that the phosphorus and sodium in the raw materials are in a normal stoichiometric ratio, that is, no sodium phosphate coating is performed, and no magnesium is doped.

[0059] By testing and analyzing product morphology and battery cycle performance:

[0060] (1) SEM image of magnesium-doped sodium fluoroferric phosphate material coated with carbon and sodium phosphate

[0061] SEM is the most basic test method for observing the microscopic morphology of materials. The present invention uses a scanning electron microscope of the model GEMINI 500 of ZEISS of Germany to characterize the surface morphology of the sample prepared in Example 1. In order to improve the conductivity of the material to obtain a clearer scanning image, the material needs to be sprayed with gold before testing. The SEM picture of the material is as follows Figure 2 As shown by Figure 2 It can be seen that the obtained material is spherical particles with a diameter of 2 to 3 μm and a special highly fluffy shape.

[0062] (2) Electrochemical performance test of magnesium-doped sodium fluorophosphate material coated with carbon and sodium phosphate

[0063] In order to test the electrochemical properties of the material, the material was used as the positive electrode to assemble a half-cell for electrochemical performance testing. First, 200 mg of the material prepared in Example 1 and 25 mg of SuperP were weighed respectively, ground in an agate mortar for about 20 min until fully mixed and then transferred to a paste bottle, 500 mg of the prepared 5wt% PVDF NMP solution was added, and then about 800 μL of NMP solution was added, and magnetic stirring was performed for about 12 hours until a slightly viscous paste liquid. Subsequently, a 120 μm scraper was used to evenly coat the paste on the aluminum foil, and vacuum dried at 120 ° C for 12 hours. The obtained positive electrode was formed into a positive electrode with a diameter of 12 mm by a punching machine. With the electrode as the positive electrode, the sodium sheet as the negative electrode, the glass fiber as the diaphragm, and the electrolyte selected as 1.0M NaClO4 / EC-PC (volume ratio 1:1, 5.0Vol% FEC), the CR2032 button battery was assembled in a glove box filled with argon. The button cell is charged and discharged at a constant current of 0.2C (1C = 120mAh / g), with a voltage range of 2.0 to 4.0V. The cycle curves of the button cell and the undoped sodium ferric fluorophosphate and the uncoated sodium ferric fluorophosphate are compared as shown in the figure. Figure 3 As shown in the figure, the charge and discharge curves of undoped and uncoated sodium iron fluorophosphate are compared as shown in the figure Figure 4 As shown. Figure 3 It can be concluded that magnesium doping and sodium phosphate coating are both beneficial to the improvement of cycle performance. Figure 4 It can be concluded that magnesium doping and sodium phosphate coating are beneficial to a significant improvement in the specific capacity of the material.

[0064] Table 1 Charge and discharge test results

[0065]

[0066] As can be seen from Table 1, compared with no magnesium doping (Comparative Example 1), no sodium phosphate coating (Comparative Example 2) and no magnesium doping and sodium phosphate coating (Comparative Example 3), the present invention improves the electronic conductivity of the phosphate material by magnesium doping on the basis of sodium iron fluorophosphate material, and at the same time enhances the structural stability of the material, so that the positive electrode active material has both high energy density and cycle stability. Excessive phosphate is coated with sodium phosphate in one step during the synthesis process, forming a stable interface layer on the surface of the material, reducing the occurrence of interface side reactions, and improving cycle stability. The carbon coating in the second step increases the surface electronic conductivity, achieving an improvement in the material rate performance.

Claims

1. A magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer, characterized in that The magnesium-doped sodium fluorophosphate material is Na2Fe x Mg y PO4F is the inner core, the inner core surface is covered with a sodium phosphate layer, and the outermost layer is a conductive carbon layer, wherein Fe is +2, 0.05≤y≤0.10, and x+y=1.

2. A method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 1, characterized in that The method comprises the following steps: Step 1: Mixing: A sodium source, an iron source, a magnesium source, a phosphorus source, a fluorine source and a carbon source are mixed in proportion to obtain a solid raw material mixture, wherein the ratio of each element in the solid raw material mixture is Na:Fe:Mg:P:F=2-2.5:0.85-0.99:0.01-0.15:1-1.5:1-1.5, and the carbon source accounts for 10-20% of the total mass of the sodium source, the iron source, the magnesium source, the phosphorus source and the fluorine source; Step 2: Mechanical ball milling: The solid raw material mixture and ball milling beads in step 1 are added into a ball mill for ball milling, and the ball milling product is vacuum dried; Step 3: Sintering: The material is first pre-sintered at a low temperature under the protection of an inert gas, and then subjected to secondary sintering by heating the same furnace, thereby finally obtaining a magnesium-doped sodium fluoroferric phosphate material double-coated with a carbon layer and a sodium phosphate layer.

3. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that The sodium source is at least one of sodium fluoride, sodium acetate, sodium carbonate, sodium bicarbonate, sodium citrate, sodium oxalate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium isopropoxide, sodium carboxymethyl cellulose, sodium oleate, sodium ascorbate, and sodium alginate; the iron source is at least one of ferrous oxalate, ferrous sulfate, ferrous chloride, ferric phosphate, ferric oleate, ferric citrate, ferric tartrate, and sodium ethylenediaminetetraacetic acid iron; the magnesium source is at least one of magnesium oxide, magnesium carbonate, magnesium chloride, magnesium phosphate, magnesium oxalate, magnesium gluconate, magnesium acetate, magnesium citrate, and magnesium methylate; the phosphorus source is at least one of phosphoric acid, sodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate; the fluorine source is at least one of sodium fluoride and hydrofluoric acid; the carbon source is at least one of glucose, sucrose, ascorbic acid, graphite, carbon nanotubes, polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, sodium carboxymethyl cellulose, phytic acid, stearic acid, and urea.

4. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that The mass ratio of the ball milling beads to the solid raw material mixture is 8 to 10:

1.

5. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that A liquid medium is added during the ball milling, and the liquid medium is one or more of water, ethanol, oleic acid, and N-methylpyrrolidone.

6. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that The ball mill has a rotation speed of 300 to 500 rpm and a milling time of 6 to 8 hours.

7. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that The vacuum drying is carried out at a temperature of 60 to 100° C. and for a time of 8 to 14 hours.

8. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that The process of the low-temperature pre-sintering is as follows: first, pre-pass protective gas at room temperature for 0.5 to 2 hours, then heat up to 350 to 450°C, calcine at this temperature for 2 to 6 hours, and control the heating rate to be 3 to 5°C / min; the calcination temperature of the secondary sintering is 550 to 650°C, the calcination time is 8 to 12 hours, and the heating rate is controlled to be 3 to 5°C / min.

9. The method for preparing the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and carbon layer according to claim 2, characterized in that The inert gas is one or more of argon, hydrogen, nitrogen and helium.

10. Use of the magnesium-doped sodium fluoroferric phosphate material double-coated with sodium phosphate and a carbon layer as claimed in claim 1 in a sodium ion battery.

Citation Information

Patent Citations

  • Carbon-coated sodium ferric fluorophosphate material as well as preparation method and application thereof

    CN114242968A

  • Bicontinuous phase coated ferric sodium pyrophosphate positive electrode material and preparation method thereof

    CN116565165A

  • Doped modified ferric sodium pyrophosphate positive electrode material and preparation method thereof

    CN116682946A